Corrosion behavior of Q345R steel influenced by Thiobacillus ferrooxidans. (29th October 2021) - Huang, Xin Jie; Fu, Lei; Lin, Li; Lai, Sheng; Fan, Qi; Zhang, Yingqian; Li, Xiulan; Liu, Cheng
Abstract: Here, the corrosion weight-loss method, surface analysis technology, and electrochemical test methods were used to study the corrosion behavior and electrochemical characteristics of experimental samples of Q345R steel in a sterile solution (pH 2.0) and a solution containing T. ferrooxidans . The growth cycle of T. ferrooxidans was determined to be approximately 8 days. The corrosion weight-loss method showed that the corrosion rate of Q345R carbon steel coupons decreased with time in the T. ferrooxidans system and the sterile system; the corrosion rate was approximately two times higher in the T. ferrooxidans system than in the sterile system. The corrosion morphology results showed that the presence of T. ferrooxidans promotes the corrosion of Q345R steel and increases the local corrosion of the matrix material. The electrochemical test results showed that after 5 days of corrosion, the polarization resistance of the T. ferrooxidans system was approximately 50% of that of the sterile system, and the corrosion current density of the T. ferrooxidans system was approximately twice as high as that of the sterile system. Therefore, T. ferrooxidans can accelerate the corrosion of Q345R steel two-fold.